Factores ambientales físicos y su incidencia en la aparición de pterigión en personas de 40 a 60 años Parroquia Camilo Ponce- Babahoyo- Los Ríos, octubre 2018 – abril 2019 - Jiménez Mora, Amanda Noemí (2019)
Introduction.- This research is aimed at measuring the impact of this pathology on the human being of the Camilo Ponce parish of the city of Babahoyo, and who is exposed by his daily work outdoors to the ocular pterygium, whose fundamental evidence is the franc deterioration of the conjunctiva although its actual etiopathogenesis (cause) is still unknown. Objectives.- To determine the physical environmental factors of greatest incidence in the appearance of pterygium in people with 40 to 60 years of age, Camilo Ponce, Babahoyo - Los Ríos parish, in the period of October 2018 - April 2019. Methodology.- It was a descriptive-explanatory research with a transversal design considering as a finite population the inhabitants of the Camilo Ponce parish who suffer from pterygium only, using a questionnaire of pre-elaborated questions for their technical study of the survey as an instrument. Results.- The main results of this research work among the participants is 55.56% of adults between the ages of 40 and 50 who suffer from Pterygium, there is a predominance of males / 76.19%) over females, among the participants 55.56% give importance to the care of their eyes. Conclusions.- Little importance to the care of their eyes as they are reluctant to the regular visit to optical centers for their visual control, and in search of economic savings acquire their lenses in places not recommended, risk factors in the appearance of pterygium.